HUBUNGAN PELAKSANAAN PELAYANAN PRIMA DENGAN KEPUASAN MASYARAKAT PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MALINAU - Jalung, Apriani (PREDIKSI, 2012)
Â This Research aimÂ to know what is there are Link which are positive between Prima Service with Satisfaction of Society at On duty resident and Record-Keeping Of Civil Sub-Province of Malinau.Population at this research is entire employees which is its amount counted 38 people, hence this research use census method, that is entire population made as responder.With a purpose to above, hence analyzer which is used in this research is Koefesien Correlation of Product Moment. Result of calculation between Prima Service variable with Satisfaction of Society show result of r koefesien = 0,522, showing influence between Prima Service variable with variable Satisfaction of Society in research this means that the result bigger than at r table with value of r calculate 0,522 > r of is tables of 0,413, with n = 38, singnifikasi 0,01 matter this means there are influence of link which are positive from singnifikan between prima service variable with satisfaction of society. residing in at international 0,40 - 0,599 with link level which is.Pursuant to result of calculation of test of t obtained by result of t calculate equal to 3,672, is hereinafter compared to t table with dk = 38 - 2 = 36 hence obtained by t table equal to 2,434. From the numbers look t calculate bigger than t table. Pursuant to criterion which have been specified by hence nul hypothesis in this research is refused and alternative hypothesis mentioning there are link which is signifikan between Prima Service with Satisfaction of Society at On duty resident and Record-Keeping Of Civil Sub-Province of Malinau proven and can be accepted scientifically.